Effect of Organic and Inorganic Fertilizer Combinations on the Growth and Yield of Welsh Onion (Allium fistulosum L.) in Highland Areas - Abdul Gilang Komona; Nikmah Musa; Fauzan Zakaria; Fitria S. Bagu; Laode Muhamad Irsan (International journal of technology and education research, 2026)
Welsh onion (Allium fistulosum L.) is an economically valuable horticultural commodity commonly cultivated in the highland regions of Indonesia. Despite suitable environmental conditions, its productivity remains below its potential, partly due to inefficient fertilizer management practices. This study was conducted to assess the influence of integrated organic and inorganic fertilization on the growth and yield of Welsh onion and to identify the most suitable fertilizer combination for highland cultivation. The experiment was carried out from February to May 2026 in Insil Village, Bolaang Mongondow Regency, North Sulawesi, Indonesia. A non-factorial Randomized Complete Block Design (RCBD) consisting of six fertilizer treatments and three replications was applied. The treatments included P0 (without fertilizer), P1 (1.8 t ha⁻¹ organic fertilizer + 900 kg ha⁻¹ NPK), P2 (2.7 t ha⁻¹ organic fertilizer + 750 kg ha⁻¹ NPK), P3 (3.6 t ha⁻¹ organic fertilizer + 600 kg ha⁻¹ NPK), P4 (4.5 t ha⁻¹ organic fertilizer + 450 kg ha⁻¹ NPK), and P5 (5.4 t ha⁻¹ organic fertilizer + 300 kg ha⁻¹ NPK). Experimental data were subjected to analysis of variance (ANOVA), and treatment means were compared using the Least Significant Difference (LSD) test at the 5% significance level. The findings demonstrated that integrated fertilization significantly influenced plant height, leaf production, tiller formation, and fresh biomass of Welsh onion. Among the tested treatments, P3 exhibited the most favorable overall performance in promoting both plant growth and yield. These results indicate that combining organic and inorganic fertilizers provides a balanced nutrient supply capable of enhancing Welsh onion productivity while contributing to more sustainable nutrient management practices in highland agricultural systems.